Salvage High-Intensity Focused Ultrasound for Local Recurrence in the Prostatic Bed after Prostatectomy and Adjuvant or Salvage Radiotherapy: Preliminary Results. Issue 2 (9th August 2021) - Khedime, Sarah; Gelet, Albert; Rouvière, Olivier; Lafon, Cyril; Badet, Lionel; Crouzet, Sébastien; Hostiou, Thomas
Abstract : Purpose: We sought to report the preliminary results of salvage high-intensity focused ultrasound for locally recurrent prostate cancer in the prostatic bed after radical prostatectomy and adjuvant or salvage radiotherapy. Materials and Methods: We retrospectively analyzed a single-center cohort of men treated with salvage high-intensity focused ultrasound for locally recurrent prostate cancer after radical prostatectomy and adjuvant or salvage radiotherapy. All patients had a combination of choline positron emission tomography, multiparametric magnetic resonance imaging, and transrectal biopsies to confirm the local recurrence. Treatment failure was defined as persistent or recurrent prostate cancer in the prostatic bed and/or metastasis and/or introduction of systemic treatment. Progression was defined as metastasis and/or introduction of systemic treatment. Complications (Clavien-Dindo classification) and continence (Ingelman-Sundberg score) were evaluated. Kaplan-Meier analysis estimated oncological outcomes. Results: Between July 2009 and November 2018, 22 patients were included; the median followup was 2.32 years. At 3 years, treatment failure-free survival rate was estimated to be 49.7% and progression-free survival rate 60.4%. Prostate specific antigen nadir ≤0.2 ng/ml was reached in 50% of the patients. A nadir of ≤0.2 ng/ml was significantly associated with better treatment failure-free and progression-free survival probabilities (p=0.003 and p=0.037, respectively). Grade III complications occurred in 6 patients (27.3%). Onset of grade II-III incontinence was significantly more frequent in cases of perianastomotic (36.4%) compared to retrovesical recurrence (0%; p=0.027). Conclusions: Salvage high-intensity focused ultrasound for locally recurrent prostate cancer after radical prostatectomy and salvage radiotherapy showed encouraging oncological results despite significant morbidity. The perianastomotic recurrence was linked to a higher risk of incontinence.